DAYA HAMBAT EKSTRAK KULIT DAUN LIDAH BUAYA (Aloe barbadensis Miller) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus ATCC 25923DAN Escherichia coli ATCC 25922 - Ni Kadek, Ariyanti; Ida Bagus Gede, Darmayasa; Sang Ketut, Sudirga (Jurnal Biologi Udayana; Vol 16 No 1 (2012): Jurnal Biologi)
This research aimed to determine the inhibited effect of Aloe (Aloe barbadensis Miller) rind extract to the growth of bacteria Staphylococcus aureus and Escherichia coli and the most effective concentration for the resistance against both of bacteria tested. The results showed that the extracts of Aloe rind inhibited the growth of bacteria Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. It was indicated by the formation of inhibition zones with the largest diameter average occurred concentrations of 100% with the size 11,58 mm for the Staphylococcus aureus and 6,81 mm in Escherichia coli. The highest concentration inhibited the growth of Staphylococcus aureus ATCC 25923 was 100% and 75% for the Escherichia coli ATCC 25922.
Keywords: Aloe barbadensis Miller, Escherichia coli, Staphylococcus aureus, inhibited